Pengaruh Akuisisi dan Right Issue terhadap Abnormal Return Saham - Elsye Fatmawati; Laela Nur Azizah (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
Rights issues and acquisitions are important information for shareholders that can be used to gain future profits and measure market reactions. This reaction can be measured using an abnormal return. This study aims to see whether there are significant differences before the acquisition and rights issues. The population in this study were companies listed on the IDX that carried out acquisitions and rights issues in 2015-2019. This research is a descriptive study using quantitative methods. The sample selection technique in this study is purposive sampling. By following the predetermined criteria, 9 companies were selected as samples. The type of data used is secondary data from yahoo finance 2015-2019, daily stock price data, and daily Composite Stock Price Index (IHSG) (Close Price). Hypothesis testing Paired Sample T-Test and Wilcoxon Signed Rank Test using the SPSS 22.0 program. The results of this study indicate that there is no significant difference in returns in the period before and after the announcement of the acquisition and the rights issue.